Sočasno poučevanje jezika in književnosti ob kanonski mladinski literaturi v drugem triletju osnovne šole - Mikolič, Vesna (Jezik in slovstvo, 2024)
In this article, we present the use of more modern teaching approaches, in particular the simultaneous teaching of literature and language, using the example of the short story Pehar suhih hrušk (A cup of dried pears) by Ivan Cankar in the second triennium of the elementary school. In doing so, we turn away from the established traditional approach, which focuses on the author and his psychological relationship with his mother, and direct the research focus towards the literary text and its reception. The work is interpreted using the hermeneutic method and by analysing individual elements (linguistic, stylistic, motivic-thematic, etc.) and the whole in its socio-cultural context. In this way, students are better motivated to learn both literature and language while developing reception, (meta)linguistic skills, communication skills and critical thinking.
Keywords: A cup of dried pears; didactics of Slovene; Didaktika; didaktika slovenščine; Jezikoslovje; literarna zmožnost; literary competence; nenasilna komunikacija; non-violent communication; Pehar suhih hrušk; teaching model TILKA; učni model TILKA